Realitas Bansos Hibah: Lika Liku Pilu Auditor Internal (Studi Kasus Provinsi Indraprasta) - Sari, Anggun Anita (IAIN Kudus, 2018)
This study aims to describe how the role of the government internal auditors carries out examination tasks, especially in the implementation of social assistance and grants. This study finds that the informant's efforts are actually quite persistent in conducting the audit. However, there are many factors that influence the process of inspection such as the limited human resources, the existence of legislative interest and the character of the receiver itself. Based on understanding of informant roles, there are three audit acts, the first, avoidance if audit was very high risk. Second, justification that emphasizes a neat accountability report rather than audit implementation. Third, safekeeping that give solution and ensure that the missused funds re-deposited to the treasury funds.